FOXP3 and Regulatory T Cells in Preeclampsia: Immune Dysregulation, Mechanistic Insights, and Clinical Implications - Shweikh, Amani Katea; Alfattli, Hams Hussain H. Handool (American Journal of Biology and Natural Sciences, 2026)
Preeclampsia remains a major obstetric complication characterized by high maternal and fetal morbidity and mortality. Emerging evidence suggests that the failure to establish maternal-fetal immunotolerance is a primary driver of the disease. Regulatory T cells (Tregs), governed by the master transcription factor FOXP3, play a pivotal role in maintaining this immunological equilibrium.This review explores how diminished FOXP3 expression and Treg dysfunction trigger a hyper-inflammatory environment that impairs trophoblast invasion and prevents the physiological remodeling of spiral arteries. Unlike conventional reviews, this paper highlights the critical role of epigenetic modifications, such as FOXP3 promoter hypermethylation, in the loss of Treg functional stability and their subsequent plasticity toward pro-inflammatory phenotypes.Furthermore, we propose a novel diagnostic framework integrating FOXP3 expression with angiogenic markers (sFlt-1/PlGF) as an early predictive tool. The review concludes by discussing promising therapeutic avenues, including low-dose Interleukin-2 (IL-2) immunotherapy and "immune reset" strategies, paving the way for precision medicine and personalized interventions in obstetric care.